LITERASI FITUR DATA-FORM MS. EXCEL UNTUK MENGELOLA DATABASE ANGGOTA PERKUMPULAN KEMATIAN “LAZARUS” MALANG - Tri Istining Wardani; Asminah Rachmi; Dwi Sudjanarti; Umi Khabibah; Achmad Zaini (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2022)
This community service aims to develop technical skills in managing databases. So far, the “Lazarus" commission processed all regular membership fees manually. The repetitive work and recording errors happened along the way. With a total of 428 family members out of 993, the above data processing was inefficient and ineffective. Ms. Excel, especially the Data-Form feature will make database management easier for someone to process data entry, edit, search, and delete in a database table. When a database has been formed, the preparation of the annual report will also be able to be compiled efficiently & effectively, because the database is already stored in a soft file. Community service is carried out through training assistance. The activity begins with preparing teaching modules, followed by assisting to create a table model database in Ms. Excel. Subsequently, design a Data (Entry) Form model for recapitulation. The competencies have been achieved because in the end the database management has been simulated very well using real data & problems. Therefore, the final evaluation results declared that the database management model uses the Data Form successfully to help the "Lazarus" commission maximize its service.